THE RELATIONSHIP BETWEEN TIME FACTOR AND FIGURATIVE FACTOR IN CHINESE AND ITALIAN FIGURE PAINTING IN THE 15TH CENTURY - Shi Xueyan; Zainuddin Abindinhazir, (INTERNATIONAL JOURNAL OF HERITAGE, ART AND MULTIMEDIA (IJHAM), 2024)
The Time factor used or emerged in painting is an issue that has been discussed for almost 1 century. However, there has never been any specific study related to time and figure painting. In addition, the author finds the time factor used in Italian and Chinese painting in the 15th century, which always depends on the figurative factor of the painting. So, this study is to explore the presentation of time factors in figure paintings in Italy and China from the 15th century to the 16th century and find out the rules between figurative factors and time factors in figure painting during this period.